Patterns Of Medication Prescribing In Adolescent Patients With Mental Disorders At Krakatau Medika Hospital City Of Cilegon For The Period Of January–December 2023 - Isti Dwi Pruschia; Maharani, Maharani; Dwiyarina Margarisa; Shinta Dewi Kartika; Dwi Astriani (Sean Institute, 2024)
Mental Disorders or Mental Illness is a disease that affects the sufferer's emotions, thought patterns and behavior, a term that refers to various conditions that affect feelings and mood. This study aims to determine the pattern of drug prescribing in adolescent patients with mental disorders at Krakatau Medika Hospital, Cilegon City for the period January - December 2023. This research is a descriptive study with retrospective data collection using patient medical record data. The sampling technique used in this research was Total Sampling using 61 samples. The variables used in this research are drug prescribing patterns, mental disorders, age and gender. The research results showed that the percentage of use of the Antidepressant drug class in the pattern of drug prescribing was higher than other psychopharmacological drug classes, patients received several types of drugs which were included in the Antidepressant drug group and there were combinations of drugs other than the Psychopharmaca drug class. Based on mental disorders, patients with depression are higher than other mental disorders, namely (44.30%). In the classification of adolescents aged 18 – 24 years, the highest percentage was at the age of 21 years, namely (23.00%) and gender, women experienced more mental disorders, namely 57.30%.